42 Implementing a change in practice in a different specialty via the chief registrar (CR) role. (16th November 2020) - Wienand-Barnett, S; Markham, L; Powell, R; Jones, L; Whitehead, T; Webb, L
Abstract : Junior doctor feedback from the General Medical Council (GMC) survey and quality panels has consistently highlighted poor handover in Acute Medical Unit (AMU) as a concern. Neglected handover practice has been identified as a key component of poor outcomes in root cause analyses within the unit. There was no formal handover of patients between the incoming and outgoing medical teams. Resolution of this problem was tasked to the chief registrar (CR). As an obstetrics and gynaecology registrar in the CR role there were potential benefits and barriers to taking on a project in a different specialty. The information gathering occurred over six months (surveys, focus groups, incident reporting). The implementation coincided with the COVID-19 surge. All staff were notified of the finalised plans the week before handover was implemented and key staff were individually approached to be champions. Feedback was encouraged and actively sought to highlight teething problems. The results show a clear improvement in handover practice, junior doctor support and multi-professional team working. There had been resistance from some senior clinicians to attend an evening handover in the planning stages, however, implementing change at the height of the pandemic meant that staff had to adapt rapidly to new ways of working and as a result this change was widely accepted and implemented. The next stage is to incorporate more teaching into handover practice by including 'teaching bites.' Upon starting the CR job this was presented as an unsolvable project. However, by a thorough analysis and formation of a plan for change with buy-in from the entire team we were able to affect a successful change. This demonstrates the value of seconding middle grade doctors to management roles as they can provide a crucial link between medical and management staff and coordinate vital change to improve patient safety.